2004
DOI: 10.1016/s1097-2765(04)00260-6
|View full text |Cite
|
Sign up to set email alerts
|

Pbx Marks Genes for Activation by MyoD Indicating a Role for a Homeodomain Protein in Establishing Myogenic Potential

Abstract: Skeletal muscle differentiation is initiated by the transcription factor MyoD, which binds directly to the regulatory regions of genes expressed during skeletal muscle differentiation and initiates chromatin remodeling at specific promoters. It is not known, however, how MyoD initially recognizes its binding site in a chromatin context. Here we show that the H/C and helix III domains, two domains of MyoD that are necessary for the initiation of chromatin remodeling at the myogenin locus, together regulate a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
372
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(400 citation statements)
references
References 48 publications
26
372
2
Order By: Relevance
“…The synergism between Arx, Mef2C and MyoD could result from a specific recognition event between the multiprotein complex and a component of the transcriptional machinery or it could result from a concerted reaction in which the assembly of the three factors stabilizes a transcriptional complex, similarly to what was reported for MyoD and Pbx, the latter containing a homeodomain like Arx. 28 The data presented here also show that Arx and Myogenin can upregulate each other's expression. Similarly, Mef2 gene products also regulate Myogenin expression 9,29 and the Mef2 genes are known targets of the myogenic basic helix-loophelix (bHLH) (24).…”
Section: Discussionsupporting
confidence: 64%
“…The synergism between Arx, Mef2C and MyoD could result from a specific recognition event between the multiprotein complex and a component of the transcriptional machinery or it could result from a concerted reaction in which the assembly of the three factors stabilizes a transcriptional complex, similarly to what was reported for MyoD and Pbx, the latter containing a homeodomain like Arx. 28 The data presented here also show that Arx and Myogenin can upregulate each other's expression. Similarly, Mef2 gene products also regulate Myogenin expression 9,29 and the Mef2 genes are known targets of the myogenic basic helix-loophelix (bHLH) (24).…”
Section: Discussionsupporting
confidence: 64%
“…26 PBX1 is known to act as co-factor for MyoD as well as Hox. 27 Binding of PBX1 to the MyoD-dependent promoter occurs before MyoD binding, then muscle differentiation starts. 27 From these findings, it is postulated that PBX penetrates into condensed chromatin and changes the local condition from silent to active stage ready for binding of gene-specific transcription factor.…”
Section: Discussionmentioning
confidence: 99%
“…27 Binding of PBX1 to the MyoD-dependent promoter occurs before MyoD binding, then muscle differentiation starts. 27 From these findings, it is postulated that PBX penetrates into condensed chromatin and changes the local condition from silent to active stage ready for binding of gene-specific transcription factor. 27,28 The fluorescent immunohistochemical analysis showed the co-localization of PBX1 and VCP in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, exogenous MyoD in endodermal and ectodermal cells failed to induce a full phenotypic switch (Weintraub et al 1989;Sch€ afer et al 1990). Later studies revealed that MyoD induces myogenin through cooperation with the Pbx factor, which is constitutively bound to MyoD target sites in fibroblasts prior to MyoD expression (Berkes et al 2004). There are many other examples of direct cell conversion within the same germ layer: the combination of PU.1 and C/EBPa into macrophage-like cells from fibroblasts (Feng et al 2008) and GATA4, MEF2C, TBX5, Hand2, and NKX2.5 for cardiomyocytelike cells from fibroblasts (Ieda et al 2010;Addis et al 2013).…”
Section: Espinosa and Emerson 2001mentioning
confidence: 99%